preparation and characterization of new sol–gel hybrid inulin–TEOS adsorbent - Hartina, Mohd Yusop; Annur Isma Husna, Mohd Ismail; Wan Norfazilah, Wan Ismail (MDPI, 2021)
A new biopolymer–silica hybrid material consisting of inulin and tetraethoxysilane (TEOS) for use as an adsorbent was successfully synthesized via the sol–gel method in acidic conditions. The hydrolysis and condensation processes were attained in water/ethanol solution. Three molar ratios of inulin:TEOS (1:1, 1:2, and 2:1) were prepared and dried at various temperatures (50, 60, and 70 °C). The optimized molar ratio of 2:1 with a drying temperature of 70 °C was found to obtain the best morphology and characteristics for absorbent properties. Fourier transform infrared spectroscopy (FTIR) analysis showed a strong interaction between inulin and TEOS, which was also observed using energy dispersive X-ray spectroscopy (EDX). Field emission scanning electron microscopy (FESEM) images revealed the presence of nanoparticles on the rough surface of the hybrid sol–gel. X-ray diffractometer (XRD) analysis showed the amorphous state of the silica network where the inulin existed as an anhydrous crystalline phase. Brunauer–Emmet–Teller (BET) analysis confirmed that the composite was mesoporous, with 17.69 m2/g surface area and 34.06 Å pore size. According to thermogravimetric analysis (TGA) results, the hybrid inulin-TEOS adsorbent was thermally stable under a temperature of 200 °C.